Muslim Immigrant Identifications in Mexico’s YouTube Sphere - Hasif, Nik (2023)
This paper examines the expression of Muslim identity on YouTube and how these identifications are received by Mexican audiences online. Taking a digital ethnographic approach, the research uses inductive content analysis of videos produced by, or featuring, Muslim immigrants. The results indicate that Muslim immigrant YouTubers portray their religious identities via non-religious channels, demonstrating their distinctive identity expressions through acts of self-affirmation. The mediators of religious identity expression can be categorised into five core areas: verbal expression, Islamic names, material expression, conduct and graphics. Various factors are linked to the generally positive attitudes expressed by Mexican audiences towards Muslim immigrant YouTubers, including the latter’s fluency in Spanish, integration with Mexican culture and their perceived ability to balance ‘culture’ and ‘religion’ in their video content. The positive comments seem also to suggest a higher level of religious tolerance and a lower level of Islamophobia in Mexico.
Keywords: Identity; Immigrant; Islam; Mexico; Social Media; Youtube